Racial Stereotyping in Bruce Norris Play Script Clybourne Park (2010) - Sofiani Sofiani; Muhd. Al-Hafizh (English Language and Literature, 2020)
This thesis is an analysis of a play written by Bruce Norris, entitled Clybourne Park (2010). This study is aimed to expose the issue about racial stereotyping which is done by the white people toward the Black and to know contribution dramatic elements; character, plot (conflict), setting, and stage direction in revealing the issue of racial stereotyping. This analysis is related to the concept of Orientalism by Edward Said in the post-colonial approach and also supported by the concepts of stereotype by Gamble. The result of this analysis is to expose the forms of stereotype toward black people. White sees blacks as poor people and black as a barbaric group.